Detection and Prevention of Wormhole & Black Hole Attacks in MANET Using AODV Protocol: Review - Sharma, R; Thakur, R (International Journal of Computer Sciences and Engineering, 2018)
Mobile ad-hoc networks are the self-configuring mobile nodes which are connected through the wireless links with the decentralised networks. The nodes in MANET communicate with each other on the basis of mutual trust. Nodes dynamically form a temporary network and are protected using many firewalls and encryption software. But number of them is not sufficient and effective. So the main aim is to provide security services such as authentication, confidentiality, integrity, availability etc. to the mobile users. In this paper the effect of Black hole attack and Worm attack is analysed on the AODV routing protocol in MANET and prevention mechanism is presented to secure the network.